Evaluation of potato nitrogen status based on polyphenol and chlorophyll leaf content - Coelho, Fabrício Silva; Fontes, Paulo Cezar Rezende; Finger, Fernando Luiz; Cecon, Paulo Roberto (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of N rates on physiological indexes related to nitrogen nutrition in potato, and to verify the possibility of indirectly estimating leaf N contents. Flavonol (FLVI), chlorophyll (CHLI), and the nitrogen balance (NBI) indexes were evaluated, and estimations of leaf N contents were made at 21 and 42 days after emergence using the Dualex leaf‑clip instrument. The experiment was carried out from November 2010 to February 2011, in a randomized complete block design, with five N rates (0, 50, 100, 200, and 300 kg ha-1 of N, applied as urea) at pre‑planting, and four replicates. There was an increase in CHLI and NBI and a decrease in FLVI with the increasing N doses. The indexes determined with Dualex were correlated with N and extractable chlorophyll content in the fourth leaf and with potato tuber yields. Dualex can be used to evaluate N nutritional status in potato plants, and for the prognosis of final tuber yield with readings.
Keywords: Solanum tuberosum; real‑time evaluation; nutritional balance; chlorophyll; phenolic compounds; flavonols